The Influence of Personal Branding, Brand Image, and Price on Purchase Decisions on Mother of Pearl Cosmetics Brand - Vashelda, Ardhelia Denis; Wijayaningsih, Rini; Handayani, Milda (PT.KARYA GEMAH RIPAH, 2025)
This research aims to examine the influence of personal branding, brand image and price on purchasing decisions for the mother of Pearl cosmetic brand. The population in this study were all consumers who had purchased Mother of Pearl cosmetic products at the Sociolla outlet, Summarecon Mall Bekasi. The variables used in this research are Personal Branding, Brand Image, and Price as independent variables; and Purchasing Decisions as the dependent variable. The sampling technique used is the survey method and uses a questionnaire instrument. The analytical methods used are Descriptive Statistical Analysis, Data Quality Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Testing. The results of this research show that partially the variables Personal Branding, Brand Image and Price have a significant and positive influence on purchasing decisions for Mother of Pearl cosmetic products at Sociolla Summarecon Mall Bekasi. The research results from 100 respondents also indicate that, simultaneously, the variables Personal Branding, Brand Image, and Price collectively have a significant and positive influence on Purchase Decision for Mother of Pearl cosmetic products at Sociolla Summarecon Mall Bekasi. This is evidenced by the F-test results, which show a significant value of 0.000 < 0.05 and an F-value of 14.871 > 2.70, meaning that H4 is accepted and H04 is rejected. The conclusion is that Price, Brand Image, and Personal Branding simultaneously influence the purchase decision of Mother of Pearl cosmetic products.